2019
DOI: 10.1101/794495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural effects and functional implications of phalloidin and jasplakinolide binding to actin filaments

Abstract: Actin undergoes structural transitions during polymerization, ATP hydrolysis and subsequent release of inorganic phosphate. Several actin binding proteins sense specific states during this transition and can thus target different regions of the actin filament. Here we show in atomic detail that phalloidin, a mushroom toxin that is routinely used to stabilize and label actin filaments, suspends the structural changes in actin, likely influencing its interaction with actin binding proteins. Furthermore, high-res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
1
6
1
Order By: Relevance
“…1C). Interestingly and contrary to what we have 110 seen before in samples co-polymerized with phalloidin (Pospich et al, 2019), the D-loop is in 111 its closed conformation ( Fig. S3).…”
Section: Structure Of the Lifeact-f-actin Complex 89contrasting
confidence: 72%
See 3 more Smart Citations
“…1C). Interestingly and contrary to what we have 110 seen before in samples co-polymerized with phalloidin (Pospich et al, 2019), the D-loop is in 111 its closed conformation ( Fig. S3).…”
Section: Structure Of the Lifeact-f-actin Complex 89contrasting
confidence: 72%
“…Based on previous studies (Mentes et al, 2018;Merino et al, 2018b;Pospich et al, 2019), we 90 know that phalloidin stabilizes actin filaments. When it is added during polymerization, the 91 nucleotide binding pocket is occupied with an ADP and Pi and the D-loop is in the open 92 conformation (Pospich et al, 2019). We therefore polymerized actin in the presence of 93 phalloidin and added an excess of Lifeact to the formed filaments in order to fully decorate the 94 filaments with Lifeact.…”
Section: Structure Of the Lifeact-f-actin Complex 89mentioning
confidence: 70%
See 2 more Smart Citations
“…Consistent with this notion, we showed that modification of filaments by the actinstabilizing drugs jasplakinolide and phalloidin have different effects on the binding dwell-time of utrophin ABD mutants. Recent evidence has suggested that jasplakinolide preferentially biases one state of f-actin, stabilizing the D-loop from subdomain 2 in a more open configuration (Pospich et al, 2019), which may partially explain our observations. CH1-CH2 domains have been shown to bind actin by making contacts both on and between actin subunits within the same protofilament (Iwamoto et al, 2018;Kumari et al, 2019) (n and n+2).…”
Section: Discussionsupporting
confidence: 67%